Texts formalization for technological purposes (Eurasian Journal of Philology Science and Education, 2018)
The author tried to expand transformational grammar, adding to its hierarchical relationships among sentence components. That is to say, studying sentence structure from the inside in order to teach the construction of sentences through the help of these structural models.